Lianas reduce carbon accumulation and storage in tropical forests - van der Heijden, Geertje M.F.; Powers, Jennifer S.; Schnitzer, Stefan A. (National Academy of Sciences, 2015)
Tropical forests store vast quantities of carbon, account for a third of the carbon fixed by photosynthesis, and are a major sink in the global carbon cycle. Recent evidence suggests that competition between lianas (woody vines) and trees may reduce forest-wide carbon uptake. However, estimates of the impact of lianas on carbon dynamics of tropical forests are crucially lacking. Here, we used a large-scale liana removal experiment and found that, three years after liana removal, lianas reduced net above-ground carbon uptake (growth and recruitment minus mortality) by ~76% per year, mostly by reducing tree growth. The loss of carbon uptake due to liana-induced mortality was 4-times greater in the control plots were lianas were present, but high variation among plots prevented a significant difference among the treatments. Lianas altered how aboveground carbon was stored. In forests where lianas are present, the partitioning of forest aboveground net primary production is dominated by leaves (53.2% compared to 39.2% in liana-free forests) at the expense of woody stems (from 28.9% compared to 43.9%), resulting in a more rapid return of fixed carbon to the atmosphere. After three years of experimental liana removal, our results clearly demonstrate large differences in carbon cycling between forests with and without lianas. Combined with the recently reported increases in liana abundance, these results indicate that lianas are an important and increasing agent of change in the carbon dynamics of tropical forests.